2021
DOI: 10.1097/rti.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Time and Patient Radiation of Computed Tomography–guided Thoracic Needle Biopsies With Single-rotation Axial Acquisitions

Abstract: Purpose: To investigate the effect on procedure time and patient radiation indices of replacing helical acquisitions for needle guidance during thoracic needle biopsy (TNB) with intermittent singlerotation axial acquisitions. Materials and Methods:This retrospective intervention study included 215 consecutive TNBs performed by a single operator from 2014 to 2018. Characteristics of patients, lesions, and procedures were compared between TNBs guided only by helical acquisitions initiated in the control room (he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The shorter procedure time afforded by realtime CT, often referred to as "CT fluoroscopy, " creates time for ROSE and the collection of additional samples [32]. A minimum of at least four tissue cores was recommended by the panel, exceeding the minimum of three recommended by the CAP guideline since research has demonstrated that sensitivity for histopathologic diagnosis and molecular testing increases significantly between the second and fourth samples [24,[33][34][35]. ROSE remains best practice according to the literature [36], despite the limitations noted by the panel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shorter procedure time afforded by realtime CT, often referred to as "CT fluoroscopy, " creates time for ROSE and the collection of additional samples [32]. A minimum of at least four tissue cores was recommended by the panel, exceeding the minimum of three recommended by the CAP guideline since research has demonstrated that sensitivity for histopathologic diagnosis and molecular testing increases significantly between the second and fourth samples [24,[33][34][35]. ROSE remains best practice according to the literature [36], despite the limitations noted by the panel.…”
Section: Discussionmentioning
confidence: 99%
“…The National Cancer Institute Molecular Analysis for Therapy Choice trial similarly recommends splitting each core into two specimens, one for diagnosis and one for ancillary studies such as molecular testing [40]. During ROSE, pathologists and cytotechnologists should use specific terminology to distinguish between "diagnostic adequacy" versus "ancillary testing adequacy" [33]. Optical coherence tomography may, one day, be used to perioperatively quantify viable tumor cells versus scar in tissue cores [41].…”
Section: Discussionmentioning
confidence: 99%
“…With 16 to 64 multidetector row CTs, the biopsies were performed using intermittent axial acquisitions triggered with a foot pedal at the scanner, akin to the previously described "single-rotation" technique for needle guidance. 19 The recovery protocol consisted of 2 hours of continuous vital sign monitoring in bed, with the biopsied side in a dependent position, and with portable chest radiographs obtained before and after. In the absence of complications, patients were discharged 2 hours after completion of the procedure.…”
Section: Biopsy Techniquementioning
confidence: 99%
“…Therefore, CT is commonly used to guide percutaneous thoracic needle biopsies and thermal ablations. [2][3][4][5][6] Reasons to consider guidance with MR instead of CT include limiting ionizing radiation, especially for children and young adults. In the helical mode, reported median radiation exposure of CT-guided thoracic needle biopsies and thermal ablations amount to dose length products of 569 and 1446 mGy×cm, respectively.…”
mentioning
confidence: 99%
“…Compared with MRI, computed tomography (CT) offers fast image acquisition, is less expensive, and is widely available. Therefore, CT is commonly used to guide percutaneous thoracic needle biopsies and thermal ablations 2–6…”
mentioning
confidence: 99%